The Contribution of Picture Media towards the English Language Competency of the Seventh Grade Students of SMP N 1 Singaraja in relation to the Implementation of Curriculum 2013 in 2013/2014 - ., Made Seni Ryana; ., Drs.Gede Batan,MA; ., I Putu Ngurah Wage M, S.Pd. (Jurnal Pendidikan Bahasa Inggris undiksha, 2013)
The aim of this study were to find out (a) significant difference of English language competency of between the students who learnwith picture mediain a scientific approach and those who learn without picture media; (b) to find out the students’ responses towards the use of picture media in learning English based on the scientific approach. The resultwas an experimental with a post-test control group design. The population of this study consisted of 236 students eight different classes. There were 60 students selected as the sample using cluster random sampling divided into a control group and an experimental group. The data of the study were collected by using test, questionnaires, and observation check list. The analysis of the quantitative data was carried out by using descriptive and inferential statistics, while the analysis of the qualitative data were made descriptively. The results indicated that: (a) there was a significant different of English language competency between the students who were taught with picture media. This meant that picture media used based on the scientific approach contributed significantly the English language competency of the students at the seventh grade of SMP Negeri 1 Singaraja. (b) The students’ development of scientific attitude based on the results it was recommended for the teacher to implement the scientific approach supported by picture media,. Kata Kunci : picture, English Language, Scientific Approach The aim of this study were to find out (a) significant difference of English language competency of between the students who learnwith picture mediain a scientific approach and those who learn without picture media; (b) to find out the students’ responses towards the use of picture media in learning English based on the scientific approach. The resultwas an experimental with a post-test control group design. The population of this study consisted of 236 students eight different classes. There were 60 students selected as the sample using cluster random sampling divided into a control group and an experimental group. The data of the study were collected by using test, questionnaires, and observation check list. The analysis of the quantitative data was carried out by using descriptive and inferential statistics, while the analysis of the qualitative data were made descriptively. The results indicated that: (a) there was a significant different of English language competency between the students who were taught with picture media. This meant that picture media used based on the scientific approach contributed significantly the English language competency of the students at the seventh grade of SMP Negeri 1 Singaraja. (b) The students’ development of scientific attitude based on the results it was recommended for the teacher to implement the scientific approach supported by picture media,. keyword : picture, English Language, Scientific Approach